The Diversity of Reptile Species in Mangrove Ecotourism of Kampung Rawa Mekar Jaya, Siak Regency - Aldi Ardiansyah Putra; Defri Yoza; Sri Catur Setyawatiningsih (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2023)
Rawa Mekar Jaya mangrove ecotourism is the last mangrove forest on the east coast of Sumatra Island. This mangrove forest is a home for reptiles. The reptilian fauna of the Mekar Jaya mangrove has the potential to become an ecotourism object. This study aims to determine the diversity, evenness, abundance, and status of reptile species in the Mekar Jaya mangrove ecotourism. Four 3 x 400 m transects were conducted in two habitat types: aquatic (10 m of bank) and terrestrial (30 m of bank). Observations were made in the morning and evening at low tide and repeated five times at three-day intervals. Direct collection of reptile data using a visual survey (VES) and passive sampling (glue trap). The researchers managed to capture 52 individuals, which were reptiles, consisting of 4 species (Draco sumatranus, Hemidactylus platyurus, Mabuya multifasciata, and Varanus savator) found directly in the field. The results of the interviews with the managers indicate that there are 2 species of crocodiles: Crocodylus porosus and Tomistoma schlegelii. Shannon-Wiener diversity index value was medium (H'=1.02). Evenness index was labile (0.57). The highest species abundance was M. multifasciata (0.65), while the lowest abundance was H. platyurus (0.12). All reptile species found were not protected. V. salvator is classified as a low-risk species (LC/Minor Concern) and is listed in Appendix II of CITES. Two crocodile species reported by the community are protected. T. schlegelii is vulnerable and listed in Appendix I of CITES. C. porosus is low-risk and listed in CITES Appendix II.